Harmonisasi Masyarakat Dan Pemerintah Untuk Mengatasi Deforestasi Di Selatan Tulungagung - Roro Utari Indra Dewi; Alfan Zuhaiery; Ninda Halimatus Sa’diyah; Tasya Fatchiati Rizqiya; Hany Nurpratiwi (Universitas 45 Surabaya, 2023)
Deforestation is a forest condition where the forest has decreased due to human activities. The damage caused will have environmental and social impacts that will be felt by the community. The research method used is descriptive qualitative method obtained based on the results of observations, interviews, and literature studies. The results showed that in 2013-2014 the amount of deforestation in Indonesia was at 397,370 ha, in 2014-2015 it was at 1,092,181 ha which was the most extensive amount of deforestation in Indonesia's history, then in 2016 - 2020 Indonesia's deforestation area decreased drastically to reach number 111,459. This drastic decrease is due to the harmonization of the government and the community to jointly resolve this case where by 2020 the amount of deforestation in Indonesia has decreased by 82%. An extraordinary achievement from the government and society.